The contemporary Irish short story: identities in transformation - Prudente, Patrícia de Aquino (2019)
Since very early in history the people from Ireland have shown interest in narrating themselves and their land. This interest increased when the question of national identity grew stronger in Europe after the French Revolution. In the Irish context, there has been since then, and especially at the beginning of the twentieth century, a great investment from writers and literary movements in contributing to the creation of an Irish national identity. The research for this doctoral thesis evidences that the relationship between literature and national identity in Ireland still persists in the beginning of the twenty-first century. This thesis evaluates how current Irish literature (re)constructs the characteristics of national identity, dialogues with traditions, and proposes new possibilities for the future of national identity question. Eight short stories were chosen from the period of the end of the twentieth century and the beginning of the twenty-first, and were analysed in the light of Stuart Hall and Mikhail Bakhtins theories to reveal the formative process of identity relations through (non)identifications between the literary text and the varied discourses on the Irish nation.